2020
DOI: 10.1002/path.5420
|View full text |Cite
|
Sign up to set email alerts
|

A streamlined mass spectrometry–based proteomics workflow for large‐scale FFPE tissue analysis

Abstract: Formalin fixation and paraffin-embedding (FFPE) is the most common method to preserve human tissue for clinical diagnosis, and FFPE archives represent an invaluable resource for biomedical research. Proteins in FFPE material are stable over decades but their efficient extraction and streamlined analysis by mass spectrometry (MS)-based proteomics has so far proven challenging. Herein we describe a MS-based proteomic workflow for quantitative profiling of large FFPE tissue cohorts directly from histopathology gl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 53 publications
2
97
0
Order By: Relevance
“…Alongside, strategies were developed to perform proteomics by AR combined with enzymatic digestion (most often trypsin) from FFPE (37,38). Protocols have been optimized over the years and nowadays thousands of proteins can be identi ed from archived tissues (39). In 2007, strategies were also proposed to unlock mass spectrometry imaging (MSI) of proteins from FFPE tissues (21) and nowadays protocols for protein analysis from FFPE tissue are highly reproducible (23).…”
Section: Discussionmentioning
confidence: 99%
“…Alongside, strategies were developed to perform proteomics by AR combined with enzymatic digestion (most often trypsin) from FFPE (37,38). Protocols have been optimized over the years and nowadays thousands of proteins can be identi ed from archived tissues (39). In 2007, strategies were also proposed to unlock mass spectrometry imaging (MSI) of proteins from FFPE tissues (21) and nowadays protocols for protein analysis from FFPE tissue are highly reproducible (23).…”
Section: Discussionmentioning
confidence: 99%
“…The field of MS-based analysis of clinical FFPE material is developing rapidly and currently receiving much attention in particular in the field of cancer diagnostics. [18] While the applicability for diagnosis may yet be limited, this approach represent a highly valuable complementary tool to classical tissue histology analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Advances in mass spectrometry (MS)-based analysis of proteins extracted from FFPE biopsies is paving way for the use of archival clinical material collected for pathology assessment to perform tissue proteome analysis. [18] We recently demonstrated that proteome analysis of FFPE tissue sections from untreated and treated coeliac disease patients accurately captures disease hallmarks and processes that we know change upon disease remission. [19] By use of laser-capture microdissection (LCM), specific regions or compartments can be isolated from FFPE tissue sections for proteome analysis.…”
Section: Introductionmentioning
confidence: 99%
“…While actual single-cell proteomics of human livers have not been done yet, recent technological advances has opened up for large-scale proteomics in formalin-fixed, paraffinembedded liver biopsy tissue, with great promise for further understanding of hepatic cells' functional contributions to liver biology [82].…”
Section: Cell-type Resolved Proteomicsmentioning
confidence: 99%